(untitled) (Modern education and development, 2025)
The objective of this research is to explore the language register utilized during the Victorian Era. It aims to address three key questions: 1) How did the Industrial Revolution influence language choices in this period? 2) What expressions of language register were prevalent during the Victorian Era? This study employs a qualitative descriptive approach, utilizing content analysis to examine the context, intentions, and messages conveyed in communication. It involves analyzing and drawing conclusions about the speakers as the addressors and the audience as the addressees of the texts. The research highlights societal issues of the Victorian Era, particularly the challenging circumstances faced by orphans and children during the Industrial Revolution, which serves as a central focus. Additionally, it emphasizes realism through its portrayal of authentic characters and settings, detailed depictions of daily life, believable plots, community dialects, character development, and the significance of illustrating social class.